Biofuel production from Euglena: Current status and techno-economic perspectives. (March 2023) - Kim, Sunah; Im, Hyungjoon; Yu, Jaecheul; Kim, Keunho; Kim, Minjeong; Lee, Taeho
Graphical abstract: Highlights: Lipid and wax ester in Euglena are promising sources for microalgae-based biofuel. Cost of jet biofuel production from Euglena is not currently viable on large scale. Improving productivity and downstream efficiency is needed for economic production. Valorization of food byproducts to medium can be an option for cost reduction. Abstract: Sustainable aviation fuels (SAFs) can contribute reduce greenhouse gas emissions compared to conventional fuel. With the increasing SAFs demand, various generations of resources have been shifted from the 1st generation (oil crops), the 2nd generation (agricultural waste), to the 3rd generation (microalgae). Microalgae are the most suitable feedstock for jet biofuel production than other resources because of their productivity and capability to capture carbon dioxide. However, microalgae-based biofuel has a limitation of high freezing point. Recently, a jet biofuel derived from Euglena wax ester has been paying attention due to its low freezing point. Challenges still remain to enhance production yields in both upstream and downstream processes. Studies on downstream processes as well as techno-economic analysis on biofuel production using Euglena are highly limited to date. Economic aspects for the biofuel production will be ensured via valorization of industrial byproducts such as food wastes.